Colonization by mites of glacier-free areas in King George Island, Antarctica Colonização por ácaros em áreas livres de geleiras na Ilha Rei George, Antárctica - Grzegorz Gryziak (Pesquisa Agropecuária Brasileira, 2009)
This work aimed to investigate the ratio of colonization by terrestrial mites on ice-free areas created by the ongoing climate-induced melting of Antarctic glaciers. Glacier retreat opens new ice-free areas for the colonization by vegetation and animals. The study was undertaken on the Antarctic Specially Protected Area no. 128 (West Coast of the Admiralty Bay, King George Island, South Shetlands Islands). Transects marked between the Ecology, Baranowski and Windy Glaciers, and a sea shore were used to collect soil samples. Oribatid mites were found only on near-shore areas, on patches of vegetation of more than 30 years of age. The colonization by mite communities is strongly determined by the presence of plants. Este trabalho visou investigar a proporção de colonização, por ácaros terrestres, em áreas de terra seca criadas pelo contínuo derretimento das geleiras antárticas induzido pelas condições climáticas. O recuo das geleiras abre novas áreas livres de gelo para a colonização pela vegetação e por animais. O estudo foi conduzido na Área de Proteção Especial da Antártica número 128 (ASPA nº 128, costa oeste da Baía do Almirantado, Ilha Rei George, Ilhas Shetland do Sul). Transectos marcados entre as geleiras Ecology, Baranowski e Windy e a costa marítima foram utilizados para coletar amostras de solo. Os ácaros oribatídeos foram encontrados somente em áreas próximas da costa em manchas de vegetação com mais de 30 anos de idade. A colonização das áreas de terra pelas comunidades de ácaros é fortemente determinada pela presença de plantas.